Letting Go To Become Whole, Celebrating The Love-Sorrow Theopoetics Through the Mystical Path of Meister Eckhart in the Song “I Love You But I’m Letting Go” by Pamungkas - Josua Estomihi Butarbutar; August Corneles Tamawiwy (Studia Philosophica et Theologica, 2026)
This article explores the concept of radical letting go (Gelassenheit) as a path to self-wholeness, integrating the mysticism of Meister Eckhart and the theopoetics proposed by John D. Caputo, using the song "I Love You But I'm Letting Go" (Pamungkas) as a case study. Letting go—whether in human relationships, images of God, or the ego—is analyzed as an act of liberating faith, where love-sorrow—simultaneously wound and love—becomes the sacred space for divine birth. Through a radical hermeneutic approach, the study reveals that: Detachment (Abgeschiedenheit) and the emptiness of the soul are prerequisites for union with the Divine (Grunt/ground). Furthermore, Pamungkas' song reflects the dynamics of creatio ex profundis—the birth of meaning from chaos (tehom), aligning with Caputo's critique of creatio ex nihilo. Additionally, trauma and wounds are not failures, but living witnesses that shape true identity and open space for "the impossible." Finally, the act of "letting go" is a contemporary liturgy celebrating fragility, simultaneously responding to the divine "insistence" that works within the uncertainty of an event. In conclusion, the theopoetics of this song offer a paradox where wholeness is achieved precisely through total release—even from images of God and self—allowing humans to become a "home" for the Divine that celebrates life in freedom, fragility, and wholeness.